Expansive and Invasive: Mapping the “Bossware” Used to Monitor Workers - Munn, Luke (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2024)
“Bossware” is software that monitors workers, tracking their activity and productivity in often hidden ways. This type of software has seen a surge of interest since the start of the pandemic, as managers attempt to retain oversight of workers in remote or distributed conditions. However, “bossware” is not monolithic but highly differentiated, with each product created by specific companies, with specific affordances, for specific purposes. This article thus builds a more articulated portrait of bossware by mapping the landscape. It first defines a schema based on the “expansiveness” and “invasiveness” of this software and maps key products along these two axes. It then develops a bossware typology ranging from spyware through to soft-bossware and productivity-ware, highlighting their differences in terms of data captured, userbases, perceived legitimacy, and existing safeguards. The article concludes by offering several approaches to investigating these technical regimes and stressing bossware as a site of both power and counterpower.